Improvement of rhythm sight-reading through the use of the Eastman Breath Impulse method - Freed, Joanna (Kansas State University, 2022)
The lessons included in this report focus on the use of the Eastman Breath Impulse Method in order to improve my concert band’s sight-reading skills. This method breaks rhythms down into beat notes and pulse notes. The beat note is the type of note that receives the beat as dictated by the bottom number of the time signature, and the pulse note is the subdivision. In my lessons, the beat note was the quarter note and the pulse note was the eighth note. Besides highlighting the subdivisions within notes, this method also helps to establish the connection of the pulsing of the eighth note with the tapping of the foot. This is just another reinforcement of the pulse and subdivision. As a class we went through a variety of rhythms using this system, beginning with how to write the counts and breath impulse markings underneath the notes, clapping and counting rhythms, then sizzling them with the pulses while fingering the notes, and finally playing them. Both the students and I noticed improvement in their rhythm reading skills by applying this method. Throughout my coursework during my Master’s degree program, I have learned of various techniques and methods in order to improve my ensembles’ overall music skills. Although I had a strong foundation from my undergraduate degree, several of my classes have caused me to reflect on how I can be more effective in my instruction in order to create more self-sufficient musicians. For example, a good amount of time was spent in my Advanced Rehearsal Techniques course on how to shape our warm-up time in order to not only get students focused and physically ready but to also teach content and skills that will then be applied to the literature. My implementation of the Eastman Breath Impulse Method is a direct result of this as I continue to find techniques that will more effectively teach my students the skills that they will carry forward into the rehearsals of our concert literature. This course along with several others have also made me reflect on how I can be more efficient in my teaching and organization. Rather than taking on all responsibilities myself, I have discovered and learned ways to not only lessen my load but to also give more people ownership and responsibility for our program and accomplishments. This has obviously caused me to be less stressed but also strengthens the commitment that the other members have to the ensemble. Overall, I have developed into a more effective, efficient, calm, collected, and engaging educator as a result of my Master’s program.
Keywords: Rhythm; Sight-reading; Eastman Breath Impulse